STRATEGI KOALISI PARTAI KEADILAN SEJAHTERA DALAM PEMENANGAN PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PEKANBARU 2010-2011 - ', Wazni (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
PKS has requirements that must be observed by candidates for mayor / deputy mayor tobe carried include: having the support of political parties, the mass base of supportand success program. Because the non-fulfillment of the quota of 15 seats in parliament,PKS makes the initial coalition with Paradise as individu.Selanjutnya, the coalitioncontinued with the coalition parties combined. There are six parties joined-Versecarries Firdaus Cahyadi are: PKS, Hanura, UN, PDK, the Democratic Party and thePDI-P.Keywords: Coalition, Election, the Prosperous Justice Party.